2019
DOI: 10.17011/apples/urn.201902191584
|View full text |Cite
|
Sign up to set email alerts
|

Foreign language anxiety

Abstract: Although foreign language anxiety is a widely studied construct assumed to develop from negative experiences of language instruction, few researchers have focused on young learners in this regard. This multiple case study investigates levels and triggers of language anxiety in Swedish primary classrooms under rather favorable learning conditions with a supportive, non-competitive atmosphere, and without formal knowledge requirements or grades. A total of 225 learners, aged 8-12, studying English as their first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Seemingly, Raquel is well aware of the fact that speaking in full classes ignites students' negative emotions such as anxiety. This finding echoes the ones obtained by Nilsson (2019) who concluded that the speaking ability is the most frequent trigger of students' anxiety.…”
Section: Raquelsupporting
confidence: 88%
See 2 more Smart Citations
“…Seemingly, Raquel is well aware of the fact that speaking in full classes ignites students' negative emotions such as anxiety. This finding echoes the ones obtained by Nilsson (2019) who concluded that the speaking ability is the most frequent trigger of students' anxiety.…”
Section: Raquelsupporting
confidence: 88%
“…When trying to explain this classroom action, she admits that her perception of the students' nervousness or apprehension when the classmate could not get her meanings through might have been determining: "I look at the faces of the rest of the people and they start to become nervous". Raquel is undoubtedly aware that classfronted speaking abilities triggers negative emotions such as anxiety (Nilsson, 2019), therefore, she tactfully renounces the OCF provision probably to reestablish the tension-free and supportive classroom atmosphere.…”
Section: Think That […] You Need To Be Corrected I Think That Corrmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning anxiety to learn language skills, Nilsson (2019) acknowledges that some degree of language anxiety may be inherent in the process of foreign language learning. Despite this claim, students from the second and third year of our study, in general, did not look anxious during the learning process.…”
Section: Discussionmentioning
confidence: 99%
“…Anxious learners can suffer from anxiety in relation to a variety of aspects of the language teaching-learning process, talking to other learners, the language class, their peers' actions, and taking exams (Dewaele & Pavelescu, 2019;El-sakka, 2016;Kruk, 2019). Foreign language anxiety is correlated with a range of aspects of the teaching-learning process, instructors, language itself, speaking in front of other students, language classes, peer actions, assessments, and motivation for attitude (Nilsson, 2019). Learning can cause anxiety too.…”
Section: Figure 2 Diagram Of the Distribution Of Three Factors That Influence Students' Anxietymentioning
confidence: 99%